Multiple Resistance Mechanisms to Pyrethroids Insecticides in Anopheles gambiae sensu lato Population From Mali, West Africa. (27th April 2021) - Keïta, Moussa; Sogoba, Nafomon; Kané, Fousseyni; Traoré, Boissé; Zeukeng, Francis; Coulibaly, Boubacar; Sodio, Ambiélè Bernard; Traoré, Sekou Fantamady; Djouaka, Rousseau; Doumbia, Seydou
Abstract: Background: Insecticide-based vector control is responsible for reducing malaria mortality and morbidity. Its success depends on a better knowledge of the vector, its distribution, and resistance status to the insecticides used. In this paper, we assessed Anopheles gambiae sensu lato ( A gambiae s.l. ) population resistance to pyrethroids in different ecological settings. Methods: The World Health Organization standard bioassay test was used to assess F0 A gambiae s.l . susceptibility to pyrethroids. Biochemical Synergist assays were conducted with piperonyl butoxide (PBO), S, S, S -tributyl phosphotritioate, and diethyl maleate. L1014F, L1014S, and N1575Y knockdown resistance (kdr) mutations were investigated using TaqMan genotyping. Results: Anopheles gambiae sensu lato was composed of Anopheles arabienisis, Anopheles coluzzii, and A gambiae in all study sites. Anopheles gambiae sensu lato showed a strong phenotypic resistance to deltamethrin and permethrin in all sites (13% to 41% mortality). In many sites, pre-exposure to synergists partially improved the mortality rate suggesting the presence of detoxifying enzymes. The 3 kdr (L1014F, L1014S, and N1575Y) mutations were found, with a predominance of L1014F, in all species. Conclusions: Multiple resistance mechanisms to pyrethroids were observed in A gambiae s.l . in Mali. The PBO provided a better partial restoration of susceptibility to pyrethroids, suggesting that the efficacy of long-lasting insecticidal nets may be improved with PBO.